Synthesis and application of carbon adsorbents in chromatographic separation of biologically active complexes. Issue 2 (August 2017) - Kerimkulova, AR; Azat, Seitkhan; Manocha, LM; Manocha, SM; Mansurov, GE Zhusupova and ZA
No abstract available